(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Because milk’s components are complex, it should be processed using a combination of thermal and non-thermal methods to preserve its health benefits. Milk stability benefits from high-intensity pulsed electric fields with thermal exposure. In this review paper, the biological benefits of various milks such as cow, camel, and human milk were discussed. Camel milk increased anti-oxidant biomarkers in autistic children, reducing oxidative stress and thus improving autistic behavior. Anti-inflammatory compounds are produced by fermented dairy products like camembert cheese, which may have therapeutic benefits in Alzheimer’s disease. The relationship between whole milk and blood lipid concentrations in relation to cardiovascular risk is also discussed in this paper; the milk did not cause significant changes in blood cholesterol. Moderate consumption of whole milk may be beneficial to one’s health because it inhibits the activity of the mechanistic target of rapamycin complex 1, which is responsible for cancer cell growth. Infectious diseases, microbial resistance, and allergic disease were also discussed in this review paper.